A method for quantifying sporulation efficiency and isolating meiotic progeny in non‐GMO strains of Saccharomyces cerevisiae. Issue 6 (23rd June 2022) - Sirr, Amy; Timour, Martin S.; Cromie, Gareth A.; Tang, Michelle; Dudley, Aimée M.
Abstract: Meiotic mapping, a linkage‐based method for analyzing the recombinant progeny of a cross, has long been a cornerstone of genetic research. The yeast Saccharomyces cerevisiae is a powerful system because it is possible to isolate and cultivate the four products (spores) of a single meiotic event. However, the throughput of this process has historically been limited by the process of identifying tetrads in a heterogeneous population of vegetative cells, tetrads, and dyads followed by manual separation (dissection) of the spores contained in a tetrad. To date, methods that facilitate high throughput characterization and isolation of meiotic progeny have relied on genetic engineering. Here, we characterize the ability of the fluorescent dye DiBAC4 (5) to stain yeast tetrads and dyads as well as to adhere to spores following bulk tetrad disruption. Applications include quantitative assays of sporulation rates and efficiency by flow cytometry as well as enrichment of intact tetrads, dyads, or disrupted spores by fluorescence‐activated cell sorting  in strains that have not been genetically modified. Abstract : Take Away: In addition to its known property of staining dead cells, the fluorescent dye DiBAC4 (5) stains Saccharomyces cerevisiae tetrads and dyads. Analysis of DiBAC4 (5)‐stained sporulation cultures by flow cytometry permits accurate quantification of sporulation efficiency. Following ascus digestion and spore dissociation, DiBAC4 (5) is retained on the spore surface at levels sufficient to allow fluorescence‐activated cell sorting based isolation of individual spores. Unlike previous methods that rely on the meiosis‐specific expression of fluorescent proteins, none of the methods described require genetic modification of the strains.